Dredger fill curing agent for accelerating electroosmosis drainage, using method and dredger fill

By using electroosmotic drainage technology of graphite tailings, sucrose, main curing agent and alkali activaters in blown soil, the problem of inefficiency of traditional curing technology is solved, and efficient soil curing and construction efficiency are achieved.

CN119822706APending Publication Date: 2025-04-15SHANDONG ELECTRIC POWER ENG CONSULTING INST CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510086677.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Traditional curing technology is inefficient when dealing with high moisture content blown soil, the curing process takes a long time, cannot meet the needs of rapid construction, and requires a large amount of curing agent to be used, resulting in increased environmental pollution and cost.

Method used

A blown-fill soil curing agent that accelerates electroosmotic drainage is adopted, and the formula includes graphite tailings, sucrose, main curing agent and alkaline exciter. The soil moisture content is reduced through electroosmotic drainage, and the strength and dry shrinkage properties of the cured soil are enhanced by the interacting curing agent components.

Benefits of technology

It significantly reduces the use of curing agents and alkali exciters, improves construction efficiency, extends the service life of cured soil, improves dry shrinkage performance, and reduces crack generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822706A_ABST
    Figure CN119822706A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and provides a dredger fill curing agent for accelerating electro-osmosis drainage, a use method and dredger fill, in the curing process, graphite tailings with the corresponding mass ratio are added, the conductive efficiency of a soil body is improved, the water content of the soil body is reduced to be in the range facilitating curing through electro-osmosis drainage, and the curing efficiency of the dredger fill is improved. The usage amount of the curing agent and the alkali activator can be reduced, and the construction efficiency is improved. The cane sugar can delay the medium action of water in the geological polymerization reaction and can provide sufficient time for electroosmosis drainage. The slag, the carbide slag and the sodium alginate are added into the curing agent, and based on the interaction among the raw material components of the curing agent, the activity of all the components of the curing agent is stimulated through an alkaline environment, so that all the components react with one another, and the strength of the cured soil is enhanced. Meanwhile, the sodium alginate and the polyacrylic acid emulsion are added, so that a certain improvement effect can be achieved on the microstructure of the solidified soil, initiation and development of cracks are hindered, and air shrinkage and cracks are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a dredger fill solidifying agent for accelerating electroosmosis drainage, a use method and dredger fill. Background Art

[0002] In the field of civil engineering, especially in coastal development projects, a large amount of blown fill soil often needs to be processed. Blown fill soil is a material that is blown from the seabed or riverbed to the land through the blowing process and used for land reclamation or land improvement. Due to the particularity of its source, this material generally has the characteristics of high water content, low permeability, high compressibility and low bearing capacity; at the same time, the high water content and low permeability lead to a very slow consolidation process. In addition, the insufficient bearing capacity makes these blown fill soils unable to meet the needs of engineering construction. Therefore, the treatment of blown fill soil is an indispensable task in engineering construction, and the use of curing agents to modify blown fill soil is a common treatment method.

[0003] Traditional solidification technology often faces the problems of low efficiency and long curing process when dealing with such high-water content blown fill, and cannot meet the needs of rapid construction. For high-water content blown fill, a large amount of curing agent needs to be added, which will cause a series of problems, such as poor shrinkage performance of the solidified soil, environmental pollution and increased costs. Summary of the invention

[0004] In order to solve the above problems, the present invention proposes a dredger fill solidifying agent for accelerating electroosmosis drainage, a method of using the dredger fill, and a corresponding mass ratio of graphite tailings are added to reduce the resistivity of silt soil, improve the conductivity efficiency of the soil body, and reduce the moisture content of the soil body to a range that is convenient for solidification through electroosmosis drainage, which can reduce the usage of the solidifying agent and the alkali activator and improve the construction efficiency; the addition of sucrose can delay the medium effect of water in the geological polymerization reaction and provide sufficient time for electroosmosis drainage.

[0005] In order to achieve the above-mentioned object, in a first aspect, the present invention provides a dredger fill solidifying agent for accelerating electroosmosis drainage, which adopts the following technical scheme:

[0006] A dredger fill solidifying agent for accelerating electroosmosis drainage, the formula of the solidifying agent includes graphite tailings, sucrose, a main solidifying agent and an alkali activator; wherein the mass of the main solidifying agent is 15% to 20% of the mass of the sludge slurry, the mass of the graphite tailings is 5% to 10% of the mass of the sludge slurry, the mass of the sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 40% to 50% of the mass of the main solidifying agent.

[0007] In order to achieve the above-mentioned purpose, in a second aspect, the present invention also provides a method for using a dredger fill solidifying agent for accelerating electroosmosis drainage, which adopts the following technical scheme:

[0008] A method for using a dredger fill solidifying agent for accelerating electroosmosis drainage, using the dredger fill solidifying agent as described in the first aspect, comprising:

[0009] Before construction, clean the surface, determine the location of the metal electrode, then drive the metal electrode to the designed depth and lay the drainage pipe;

[0010] According to the silt soil engineering volume of the block, the required material mass of the block is calculated according to the proportion, and the corresponding mass of graphite tailings, sucrose, slag, carbide slag, sodium alginate, sodium silicate and polyacrylic acid emulsion is weighed;

[0011] The slag, carbide slag and sodium alginate are stirred and evenly mixed to obtain a main curing agent;

[0012] The sodium silicate and polyacrylic acid emulsion are stirred to obtain an alkali activator after being stirred evenly;

[0013] Graphite tailings and sucrose are added to the block in sequence, and then the main curing agent and alkali activator are sprayed into the silt soil with the help of a stirring device to evenly mix the main curing agent, alkali activator and silt soil; at the same time, the stirring device is moved toward the inside of the soil, and the stirring, sinking and lifting to the designed depth are repeated until the injection amount of the main curing agent and alkali activator reaches the designed required amount, and stirring and mixing are performed again;

[0014] After stirring and mixing evenly, connect the negative pole of the power supply to the metal electrode to perform electroosmotic drainage;

[0015] When the drainage time reaches the requirement, the construction is completed.

[0016] In order to achieve the above-mentioned purpose, in a third aspect, the present invention further provides a dredger fill, which adopts the following technical solution:

[0017] A dredger fill using the dredger fill solidifying agent as described in the first aspect.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The curing agent of the present invention comprises graphite tailings, sucrose, a main curing agent and an alkali activator; adding the graphite tailings in a corresponding mass ratio reduces the resistivity of the silt soil, improves the conductivity efficiency of the soil body, and reduces the moisture content of the soil body to a range that is convenient for curing through electroosmosis drainage, which can greatly reduce the usage of the curing agent and the alkali activator and improve the construction efficiency; the addition of sucrose can delay the medium effect of water in the geological polymerization reaction and provide sufficient time for electroosmosis drainage.

[0020] 2. The present invention adds slag, carbide slag and sodium alginate to the curing agent, and based on the interaction between the raw material components of the curing agent, the activities of the components of the alkaline environment stimulator are activated, so that the components react with each other to enhance the strength of the cured soil; at the same time, sodium alginate can synergistically act with the aluminosilicate covalent network formed by the alkali-activated material to refine the pore size and reduce the pore volume, thereby improving the shrinkage performance of the cured soil and reducing the generation of cracks.

[0021] 3. In the present invention, the polyacrylic acid emulsion is added to the alkali activator, which can improve the microstructure to a certain extent during the polycondensation reaction, hinder the initiation and development of cracks, and reduce shrinkage and cracks.

[0022] 4. The graphite tailings, slag and carbide slag used in the present invention are all industrial solid wastes, which can effectively utilize solid waste resources, reduce construction costs, and are beneficial to environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings in the specification that constitute a part of this embodiment are used to provide a further understanding of this embodiment. The schematic embodiments of this embodiment and their descriptions are used to explain this embodiment and do not constitute improper limitations on this embodiment.

[0024] Figure 1 This is a flow chart of the method for using the blown fill solidifying agent for accelerating electroosmosis drainage according to Example 2 of the present invention. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0026] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0027] Embodiment 1:

[0028] In view of the particularity of high-water content dredger fill, it is particularly important to research and develop more effective curing technology. The ideal curing technology should be able to improve curing efficiency, reduce the amount of curing agent used, and effectively control the generation of cracks during the curing process without sacrificing curing quality, so as to ensure that the cured soil has good engineering performance and a long service life.

[0029] In order to solve the technical problems of poor effect of high-water content dredger fill, slow curing speed, high curing cost, low strength and poor shrinkage effect in the existing dredger fill curing technology, this embodiment provides a dredger fill curing agent for accelerating electroosmosis drainage, and its formula includes graphite tailings, sucrose, a main curing agent and an alkali activator. Among them, the mass of the main curing agent is 15% to 20% of the mass of the sludge slurry, the mass of the graphite tailings is 5% to 10% of the mass of the sludge slurry, the mass of the sucrose is 3% of the mass of the main curing agent, and the mass of the alkali activator is 40% to 50% of the mass of the main curing agent.

[0030] Optionally, the main curing agent in this embodiment includes the following raw materials by mass percentage: 59.76% to 79.68% slag, 19.92% to 39.84% carbide slag, and 0.40% sodium alginate. The alkali activator includes the following raw materials by mass percentage: 83.30% to 90.90% sodium silicate and 9.10% to 16.70% polyacrylic acid emulsion.

[0031] Optional: Graphite tailings, yellow-brown, earthy, fine powder solid, main chemical components are SiO2 and Al2O3. Sucrose, white powder, odorless, easily soluble in water and glycerol, specific rotation of 66.3°~67.0°. Slag, white powder, main chemical components are CaO, SiO2 and Al2O3, mass fraction ≥90.00%, specific surface area ≥450m 2 / kg. Preferably, carbide slag is a gray-black dry powder, the main component of which is Ca(OH)2, with a mass fraction of ≥90%. Sodium alginate is a light yellow powder, insoluble in organic solvents, and soluble in water to form a viscous liquid with a viscosity of 1.05-1.15 Pa·s, a pH value of 7-8, and water-insoluble matter ≤0.10%. Sodium silicate is a translucent block glass with a molecular formula of Na2O·nSiO2, a soluble solid content ≥99.00%, an iron content ≤0.015%, an alumina content ≤0.0015%, and a modulus of 3.41-3.70. Polyacrylic acid emulsion is a milky white viscous liquid, easily soluble in water, with a pH value of 6-7, a molecular weight of 3000-5000, and a solid content ≥30%.

[0032] The functions and principles of each component are as follows:

[0033] Graphite tailings contain less graphite residue. Graphite is a good conductive material. The addition of graphite tailings can increase the electron conduction in the soil while reducing its ion and hole conduction. As the amount of graphite tailings increases, it forms an interconnected conductive network inside the soil, which can reduce the resistivity of the soil.

[0034] Sucrose can dissolve in water to form a smaller size, adhere to solid particles to hinder their contact with the alkali activator, and provide sufficient time for electroosmotic drainage. In addition, the added sucrose does not participate in the reaction, but can only delay the medium effect of water in the geopolymerization reaction, and can also fill the pores while slowing down the setting.

[0035] The main components of slag are SiO2, CaO and Al2O3. After being excited by calcium carbide slag rich in Ca(OH)2, the slag can react with Ca(OH)2 in the alkaline environment of the solidified soil to generate CSH and CAH gels, which can solidify the pores in the soil, optimize the pore structure, improve the microstructure of the solidified soil and thus increase its density. At the same time, the reaction with Ca(OH)2 consumes more weaker Ca(OH)2 in the internal reaction system of the solidified soil, reduces the dissolution of Ca(OH)2, effectively inhibits the degradation of the internal pores of the solidified soil, and thus improves the compressive strength of the solidified soil.

[0036] Calcium carbide slag is rich in Ca(OH)2, which can provide an alkaline environment for the polycondensation reaction in the solidified soil and stimulate the activity of slag. It can generate CSH gel and calcium aluminate with slag, which mainly exist in needle-shaped, flaky and flocculent forms. These products cement the soil particles to form larger particle aggregates and stronger network connections, fill the pores between particles and groups, and improve the loose structure into a dense structure of stacked structures, greatly improving the compressive strength of the solidified soil.

[0037] Sodium alginate can react with Ca in the solidified soil reaction system. 2+ and Al 3+ Cross-linking and synergistic action with the aluminosilicate covalent network formed by alkali-activated materials can refine the pore size and reduce the pore volume, thereby improving the shrinkage properties of the solidified soil and reducing the occurrence of cracks.

[0038] Sodium silicate can provide an alkaline environment for the polycondensation reaction in the solidified soil. After adding sodium silicate, Al2O3 and SiO2 in the soil are dissolved in the alkaline environment to generate SiO4 4- and AlO4 5- , and then react with Ca 2+ The combination generates CSH and CASH gels, which overlap and cement soil particles to form a grid structure, thereby improving the strength of the sample. At the same time, CSH and CASH gels mainly exist in the form of flakes and flocculations, which can effectively fill the pores between soil particles. As the reaction proceeds, the gelling substances continue to increase to form a silicon-aluminum grid structure that can enhance the bonding ability between soil particles, fill the pores between particles and groups, and improve the loose structure to a dense structure such as a mosaic, which reduces the porosity of the soil, increases the internal friction angle, and improves the cohesion to a certain extent, thereby improving the strength and density of the soil.

[0039] During the polycondensation reaction, polyacrylic acid emulsion can fill the cracks and pores of the hardened body by adsorption and overlap each other to form a network structure, which has a certain improvement effect on the microstructure, hinders the initiation and development of cracks, and reduces shrinkage and cracks.

[0040] In summary, during the solidification process, adding graphite tailings of corresponding mass ratio can reduce the resistivity of silt soil, improve the conductivity of soil, and reduce the moisture content of soil to a range that is convenient for solidification through electroosmosis drainage, which can greatly reduce the use of curing agent and alkali activator and improve construction efficiency. Sucrose can delay the medium effect of water in geological polymerization reaction and provide sufficient time for electroosmosis drainage. Slag, carbide slag and sodium alginate are added to the curing agent, and based on the interaction between the raw material components of the curing agent, the activity of each component of the alkaline environment activator is further activated to make each component react with each other to enhance the strength of the solidified soil. At the same time, sodium alginate can synergize with the aluminosilicate covalent network formed by the alkali-activated material to refine the pore size and reduce the pore volume, thereby improving the shrinkage performance of the solidified soil and reducing the generation of cracks. The addition of polyacrylic acid emulsion to the alkali activator can improve the microstructure to a certain extent during the polycondensation reaction, hinder the initiation and development of cracks, and reduce shrinkage and cracks. The graphite tailings, slag and carbide slag used in this embodiment are all industrial solid wastes, which can effectively utilize solid waste resources, reduce construction costs, and are beneficial to environmental protection.

[0041] For the curing agent in this embodiment, a number of comparative examples were experimentally conducted. The silt soil used had an initial moisture content of 34% to 58%, a plastic limit of 16.5%, and a liquid limit of 34.9%. The soil was adjusted to a corresponding moisture content for the test. The main chemical components of the soil are shown in Table 1. The cement used was ordinary silicate cement, and the grade was P·O42.5. The slag had a specific surface area of ​​450m 2 / kg, grade is S95, its main chemical components are shown in Table 2; carbide slag, after grinding, is in dry powder state, gray-black in appearance, its main chemical components are shown in Table 3; graphite tailings is yellow-brown, has an earthy luster, and is a fine powder solid, its main chemical components are shown in Table 4; sucrose is analytically pure, white crystalline powder, content ≥99.5%; sodium silicate, appearance is white solid particles; polyacrylic acid emulsion, molecular weight is 3000-5000, solid content ≥30%.

[0042] Table 1 Main chemical components and contents of silt soil

[0043]

[0044] Table 2 Main chemical composition and content of slag powder

[0045]

[0046] Table 3 Main chemical composition and content of carbide slag

[0047]

[0048] Table 4 Main chemical composition and content of graphite tailings

[0049]

[0050] Comparative Example 1:

[0051] The solidified soil in this embodiment comprises sludge slurry, cement and graphite tailings, wherein the water content of the sludge slurry is 80%, the mass of cement is 20% of the mass of the sludge slurry, and the mass of graphite tailings is 0% of the mass of the sludge slurry. After the solidified soil samples are prepared, the resistivity values ​​of the solidified soil samples at 3d, 7d, 14d and 28d are measured.

[0052] The specific process of preparing and testing the solidified soil samples is as follows:

[0053] Step 1: Calculate the required material mass according to the ratio, and weigh the corresponding mass of sludge slurry, cement and graphite tailings;

[0054] Step 2: Put the sludge slurry into a mixer, then add cement and graphite tailings in sequence, and stir with the mixer for 5 minutes until it is evenly mixed. The mixer speed is 800r / min;

[0055] Step 3: Pour the evenly mixed solidified soil into a cylindrical mold with a diameter of 50 mm and a height of 100 mm, and scrape the surface to form a sample;

[0056] Step 4: Place the samples in a standard curing box and cure for 3 to 28 days, then demould them to obtain solidified soil samples of the target curing age.

[0057] Step 5: Apply graphite on both ends of the solidified soil sample of the target age, place the electrode sheet, and connect the lead wire to the LCR digital bridge. At a current frequency of 50kHz, test the impedance |Z| of the solidified soil. The model of the LCR digital bridge is TH2828A.

[0058] Step 6: After collecting the relevant data of the solidified soil, the resistivity value is calculated by the formula ρ = |Z|·A / L. In the formula, ρ is the resistivity of the soil sample (Ω·m); |Z| is the resistance value of the soil sample (Ω); A is the area of ​​the electrode sheet (m 2 ); L is the distance between the two electrode sheets (m).

[0059] Comparative Example 2:

[0060] The solidified soil in this embodiment comprises sludge slurry, cement and graphite tailings, wherein the water content of the sludge slurry is 80%, the mass of cement is 20% of the mass of the sludge slurry, and the mass of graphite tailings is 5% of the mass of the sludge slurry. After the solidified soil samples are prepared, the resistivity values ​​of the solidified soil samples at 3d, 7d, 14d and 28d are measured.

[0061] The above-mentioned solidified soil sample preparation method and test specific process are the same as those in Comparative Example 1.

[0062] Comparative Example 3:

[0063] The solidified soil in this embodiment comprises sludge slurry, cement and graphite tailings, wherein the water content of the sludge slurry is 80%, the mass of cement is 20% of the mass of the sludge slurry, and the mass of graphite tailings is 10% of the mass of the sludge slurry. After the solidified soil samples are prepared, the resistivity values ​​of the solidified soil samples at 3d, 7d, 14d and 28d are measured.

[0064] The above-mentioned solidified soil sample preparation method and test specific process are the same as those in Comparative Example 1.

[0065] Comparative Example 4:

[0066] The solidified soil in this embodiment comprises sludge slurry, cement and graphite tailings, wherein the water content of the sludge slurry is 80%, the mass of cement is 20% of the mass of the sludge slurry, and the mass of graphite tailings is 15% of the mass of the sludge slurry. After the solidified soil samples are prepared, the resistivity values ​​of the solidified soil samples at 3d, 7d, 14d and 28d are measured.

[0067] The above-mentioned solidified soil sample preparation method and test specific process are the same as those in Comparative Example 1.

[0068] Comparative Example 5:

[0069] The solidified soil in this embodiment comprises sludge slurry, cement and graphite tailings, wherein the water content of the sludge slurry is 80%, the mass of cement is 20% of the mass of the sludge slurry, and the mass of graphite tailings is 20% of the mass of the sludge slurry. After the solidified soil samples are prepared, the resistivity values ​​of the solidified soil samples at 3d, 7d, 14d and 28d are measured.

[0070] The above-mentioned solidified soil sample preparation method and test specific process are the same as those in Comparative Example 1.

[0071] Comparative Example 6:

[0072] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 0% of the mass of the silt slurry, the mass of the sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil sample is prepared, the unconfined compressive strength of the solidified soil sample of 28 days is measured.

[0073] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0074] Slag 69.72%, carbide slag 29.88%, sodium alginate 0.40%

[0075] The base activator in this embodiment includes the following raw materials by mass percentage:

[0076] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0077] The specific process of preparing and testing the solidified soil samples is as follows:

[0078] Step 1: Calculate the required material mass according to the ratio, and weigh the corresponding mass of sludge slurry, graphite tailings, sucrose, slag, carbide slag, sodium alginate, sodium silicate and polyacrylic acid emulsion;

[0079] Step 2: Put the slag, carbide slag and sodium alginate into a mixer and stir for 5 minutes. After stirring evenly, put the main curing agent into a container and store it for later use;

[0080] Step 3: Place sodium silicate and polyacrylic acid emulsion into a beaker and stir with a glass rod for 5 minutes. After stirring evenly, let the alkaline activator stand for later use;

[0081] Step 4: Put the sludge slurry into a mixer, first add the required graphite tailings and sucrose, use the mixer to stir for 5 minutes until it is evenly mixed, the mixer speed is 800r / min, then add the required mass of main curing agent and alkali activator in turn, use the mixer to stir for 5 minutes until it is evenly mixed, and the mixer speed is 1200r / min;

[0082] Step 5: Pour the evenly mixed solidified soil into a cylindrical mold with a diameter of 50 mm and a height of 100 mm, and scrape the surface to form a sample;

[0083] Step 6: Place the sample in a standard curing box for curing for 28 days, and demold it to obtain a solidified soil sample of the target curing age.

[0084] Step 7: Measure the unconfined compressive strength of the solidified soil samples at 28 days according to the method described in the relevant industry standards and record it.

[0085] Comparative Example 7:

[0086] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 5% of the mass of the silt slurry, the mass of the sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil sample is made, the unconfined compressive strength of the solidified soil sample of 28 days is measured.

[0087] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0088] Slag 69.72%, carbide slag 29.88%, sodium alginate 0.40%

[0089] The base activator in this embodiment includes the following raw materials by mass percentage:

[0090] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0091] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 6.

[0092] Comparative Example 8:

[0093] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0094] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0095] Slag 69.72%, carbide slag 29.88%, sodium alginate 0.40%

[0096] The base activator in this embodiment includes the following raw materials by mass percentage:

[0097] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0098] The specific process of preparing and testing the solidified soil samples is as follows:

[0099] Step 1: Calculate the required material mass according to the ratio, and weigh the corresponding mass of sludge slurry, graphite tailings, sucrose, slag, carbide slag, sodium alginate, sodium silicate and polyacrylic acid emulsion;

[0100] Step 2: Put the slag, carbide slag and sodium alginate into a mixer and stir for 5 minutes. After stirring evenly, put the main curing agent into a container and store it for later use;

[0101] Step 3: Place sodium silicate and polyacrylic acid emulsion into a beaker and stir with a glass rod for 5 minutes. After stirring evenly, let the alkaline activator stand for later use;

[0102] Step 4: Put the sludge slurry into a mixer, first add the required graphite tailings and sucrose, use the mixer to stir for 5 minutes until it is evenly mixed, the mixer speed is 800r / min, then add the required mass of main curing agent and alkali activator in turn, use the mixer to stir for 5 minutes until it is evenly mixed, and the mixer speed is 1200r / min;

[0103] Step 5: Pour the evenly mixed solidified soil into a cylindrical mold with a diameter of 50 mm and a height of 100 mm, and scrape the surface to form a sample;

[0104] Step 6: Place the sample in a standard curing box for curing for 3 to 28 days, and demold it to obtain a solidified soil sample of the target curing age.

[0105] Step 7: Measure the unconfined compressive strength of the cured soil samples at 3d, 7d, 14d and 28d according to the methods described in the relevant industry standards and record them.

[0106] Comparative Example 9:

[0107] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 15% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil sample is made, the unconfined compressive strength of the solidified soil sample of 28 days is measured.

[0108] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0109] Slag 69.72%, carbide slag 29.88%, sodium alginate 0.40%

[0110] The base activator in this embodiment includes the following raw materials by mass percentage:

[0111] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0112] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 6.

[0113] Comparative Example 10:

[0114] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 20% of the mass of the silt slurry, the mass of the sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil sample is made, the unconfined compressive strength of the solidified soil sample of 28 days is measured.

[0115] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0116] Slag 69.72%, carbide slag 29.88%, sodium alginate 0.40%

[0117] The base activator in this embodiment includes the following raw materials by mass percentage:

[0118] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0119] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 6.

[0120] Comparative Example 11:

[0121] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0122] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0123] Slag 100%, carbide slag 0%, sodium alginate 0%

[0124] The base activator in this embodiment includes the following raw materials by mass percentage:

[0125] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0126] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0127] Comparative Example 12:

[0128] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0129] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0130] Slag 90%, carbide slag 10%, sodium alginate 0%

[0131] The base activator in this embodiment includes the following raw materials by mass percentage:

[0132] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0133] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0134] Comparative Example 13:

[0135] The solidified soil in this embodiment comprises silt slurry, sucrose, graphite tailings, a main solidifying agent and an alkali activator. The water content of the slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the slurry, the mass of the graphite tailings is 10% of the mass of the slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0136] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0137] Slag 80%, carbide slag 20%, sodium alginate 0%

[0138] The base activator in this embodiment includes the following raw materials by mass percentage:

[0139] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0140] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0141] Comparative Example 14:

[0142] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0143] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0144] Slag 70%, carbide slag 30%, sodium alginate 0%

[0145] The base activator in this embodiment includes the following raw materials by mass percentage:

[0146] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0147] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0148] Comparative Example 15:

[0149] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0150] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0151] Slag 60%, carbide slag 40%, sodium alginate 0%

[0152] The base activator in this embodiment includes the following raw materials by mass percentage:

[0153] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0154] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0155] Comparative Example 16:

[0156] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0157] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0158] Slag 50%, carbide slag 50%, sodium alginate 0%

[0159] The base activator in this embodiment includes the following raw materials by mass percentage:

[0160] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0161] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0162] Comparative Example 17:

[0163] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0164] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0165] Slag 79.84%, carbide slag 19.96%, sodium alginate 0.20%

[0166] The base activator in this embodiment includes the following raw materials by mass percentage:

[0167] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0168] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0169] Comparative Example 18:

[0170] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0171] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0172] Slag 69.86%, carbide slag 29.94%, sodium alginate 0.20%

[0173] The base activator in this embodiment includes the following raw materials by mass percentage:

[0174] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0175] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0176] Comparative Example 19:

[0177] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0178] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0179] Slag 59.88%, carbide slag 39.92%, sodium alginate 0.20%

[0180] The base activator in this embodiment includes the following raw materials by mass percentage:

[0181] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0182] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0183] Comparative Example 20:

[0184] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0185] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0186] Slag 79.68%, carbide slag 19.92%, sodium alginate 0.40%

[0187] The base activator in this embodiment includes the following raw materials by mass percentage:

[0188] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0189] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0190] Comparative Example 21:

[0191] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0192] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0193] Slag 59.76%, carbide slag 39.84%, sodium alginate 0.40%

[0194] The base activator in this embodiment includes the following raw materials by mass percentage:

[0195] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0196] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0197] Comparative Example 22:

[0198] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0199] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0200] Slag 79.52%, carbide slag 19.88%, sodium alginate 0.60%

[0201] The base activator in this embodiment includes the following raw materials by mass percentage:

[0202] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0203] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0204] Comparative Example 23:

[0205] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0206] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0207] Slag 69.58%, carbide slag 29.82%, sodium alginate 0.60%

[0208] The base activator in this embodiment includes the following raw materials by mass percentage:

[0209] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0210] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0211] Comparative Example 24:

[0212] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0213] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0214] Slag 59.64%, carbide slag 39.76%, sodium alginate 0.60%

[0215] The base activator in this embodiment includes the following raw materials by mass percentage:

[0216] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0217] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0218] Comparative Example 25:

[0219] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 5% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of the sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0220] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0221] Slag 69.72%, carbide slag 29.88%, sodium alginate 0.40%

[0222] The base activator in this embodiment includes the following raw materials by mass percentage:

[0223] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0224] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0225] Comparative Example 26:

[0226] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 10% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of the sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0227] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0228] Slag 69.72%, carbide slag 29.88%, sodium alginate 0.40%

[0229] The base activator in this embodiment includes the following raw materials by mass percentage:

[0230] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0231] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0232] Comparative Example 27:

[0233] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 15% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of the sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0234] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0235] Slag 69.72%, carbide slag 29.88%, sodium alginate 0.40%

[0236] The base activator in this embodiment includes the following raw materials by mass percentage:

[0237] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0238] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0239] Comparative Example 28:

[0240] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 40% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 2d is measured.

[0241] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0242] Slag 69.72%, carbide slag 29.88%, sodium alginate 0.40%

[0243] The base activator in this embodiment includes the following raw materials by mass percentage:

[0244] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0245] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0246] Comparative Example 29:

[0247] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 60% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0248] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0249] Slag 69.72%, carbide slag 29.88%, sodium alginate 0.40%

[0250] The base activator in this embodiment includes the following raw materials by mass percentage:

[0251] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0252] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0253] Comparative Example 30:

[0254] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0255] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0256] Slag 69.72%, carbide slag 29.88%, sodium alginate 0.40%

[0257] The base activator in this embodiment includes the following raw materials by mass percentage:

[0258] Sodium silicate 100%, polyacrylic acid emulsion 0%

[0259] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0260] Comparative Example 31:

[0261] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0262] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0263] Slag 69.72%, carbide slag 29.88%, sodium alginate 0.40%

[0264] The base activator in this embodiment includes the following raw materials by mass percentage:

[0265] Sodium silicate 83.30%, polyacrylic acid emulsion 16.70%

[0266] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0267] Comparative Example 32:

[0268] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0269] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0270] Slag 69.72%, carbide slag 29.88%, sodium alginate 0.40%

[0271] The base activator in this embodiment includes the following raw materials by mass percentage:

[0272] Sodium silicate 76.90%, polyacrylic acid emulsion 23.10%

[0273] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of Comparative Example 8.

[0274] Comparative Example 33:

[0275] The solidified soil in this embodiment includes silt slurry and cement, wherein the water content of the silt slurry is 40%, and the mass of cement is 5% of the mass of the silt slurry. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0276] The specific process of preparing and testing the solidified soil samples is as follows:

[0277] Step 1: Calculate the required material mass according to the proportion, and weigh the corresponding mass of sludge slurry and cement;

[0278] Step 2: Put the sludge slurry into a mixer, add the required cement, and stir it for 5 minutes until it is evenly mixed. The mixer speed is 1200r / min;

[0279] Step 3: Pour the evenly mixed solidified soil into a cylindrical mold with a diameter of 50 mm and a height of 100 mm, and scrape the surface to form a sample;

[0280] Step 4: Place the samples in a standard curing box and cure for 3 to 28 days, then demould them to obtain solidified soil samples of the target curing age.

[0281] Step 5: Measure the unconfined compressive strength of the cured soil samples at 3d, 7d, 14d and 28d according to the methods described in relevant industry standards and record them.

[0282] Comparative Example 34:

[0283] The solidified soil in this embodiment includes silt slurry and cement, wherein the water content of the silt slurry is 40%, and the mass of cement is 10% of the mass of the silt slurry. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0284] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of comparative example 33.

[0285] Comparative Example 35:

[0286] The solidified soil in this embodiment includes silt slurry and cement, wherein the water content of the silt slurry is 40%, and the mass of cement is 15% of the mass of the silt slurry. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0287] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of comparative example 33.

[0288] Comparative Example 36:

[0289] The solidified soil in this embodiment includes silt slurry and cement, wherein the water content of the silt slurry is 40%, and the mass of cement is 20% of the mass of the silt slurry. After the solidified soil samples are prepared, the unconfined compressive strength of the solidified soil samples at 3d, 7d, 14d and 28d is measured.

[0290] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of comparative example 33.

[0291] Comparative Example 37:

[0292] The solidified soil in this embodiment includes silt slurry and cement, wherein the water content of the silt slurry is 40%, and the mass of cement is 20% of the mass of the silt slurry. After the solidified soil samples are prepared, the cumulative shrinkage strains of the solidified soil samples at 1d, 3d, 7d, 14d and 21d are measured.

[0293] The specific process of preparing and testing the solidified soil samples is as follows:

[0294] Step 1: Calculate the required material mass according to the proportion, and weigh the corresponding mass of sludge slurry and cement;

[0295] Step 2: Put the sludge slurry into a mixer, add the required cement, and stir it for 5 minutes until it is evenly mixed. The mixer speed is 1200r / min;

[0296] Step 3: Pour the evenly mixed solidified soil into a 50mm×50mm×200mm rectangular parallelepiped mold, and scrape the surface to form a sample;

[0297] Step 4: Place the sample in a standard curing box for 28 days, and demold it to obtain a 28-day cured soil sample.

[0298] Step 5: Wipe the surface of the sample with a soft cloth and measure the initial length of the sample;

[0299] Step 6: Use 502 glue to stick the glass sheets to both ends of the sample. Then evenly apply Vaseline on the glass rods and arrange them evenly on the shrinkage instrument according to the length of the sample, and place the sample on the shrinkage instrument.

[0300] Step 7: Clear the dial gauges at both ends of the shrinkage meter, record the shrinkage of the sample at 1d, 3d, 7d, 14d and 21d respectively, and calculate the cumulative shrinkage strain;

[0301] Comparative Example 38:

[0302] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of the sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the cumulative shrinkage strains of the solidified soil samples at 1d, 3d, 7d, 14d and 21d are measured.

[0303] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0304] Slag 70%, carbide slag 30%, sodium alginate 0%

[0305] The base activator in this embodiment includes the following raw materials by mass percentage:

[0306] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0307] The specific process of preparing and testing the solidified soil samples is as follows:

[0308] Step 1: Calculate the required material mass according to the ratio, and weigh the corresponding mass of sludge slurry, graphite tailings, slag, carbide slag, sodium alginate, sodium silicate and polyacrylic acid emulsion;

[0309] Step 2: Put the slag, carbide slag and sodium alginate into a mixer and stir for 5 minutes. After stirring evenly, put the main curing agent into a container and store it for later use;

[0310] Step 3: Place sodium silicate and polyacrylic acid emulsion into a beaker and stir with a glass rod for 5 minutes. After stirring evenly, let the alkaline activator stand for later use;

[0311] Step 4: Put the sludge slurry into a mixer, first add the required graphite tailings and sucrose, use the mixer to stir for 5 minutes until it is evenly mixed, the mixer speed is 800r / min, then add the required mass of main curing agent and alkali activator in turn, use the mixer to stir for 5 minutes until it is evenly mixed, and the mixer speed is 1200r / min;

[0312] Step 5: Pour the evenly mixed solidified soil into a 50mm×50mm×200mm rectangular parallelepiped mold, and scrape the surface to form a sample;

[0313] Step 6: Place the sample in a standard curing box for 28 days, and demold it to obtain a 28-day cured soil sample.

[0314] Step 7: Wipe the surface of the sample with a soft cloth and measure the initial length of the sample;

[0315] Step 8: Use 502 glue to stick the glass sheets to both ends of the sample. Then evenly apply Vaseline on the glass rods and arrange them evenly on the shrinkage instrument according to the length of the sample, and place the sample on the shrinkage instrument.

[0316] Step 9: Clear the dial gauges at both ends of the shrinkage meter, record the shrinkage of the sample at 1d, 3d, 7d, 14d and 21d respectively, and calculate the cumulative shrinkage strain;

[0317] Comparative Example 39:

[0318] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of the sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the cumulative shrinkage strains of the solidified soil samples at 1d, 3d, 7d, 14d and 21d are measured.

[0319] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0320] Slag 69.72%, carbide slag 29.88%, sodium alginate 0.40%

[0321] The base activator in this embodiment includes the following raw materials by mass percentage:

[0322] Sodium silicate 100%, polyacrylic acid emulsion 0%

[0323] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of comparative example 38.

[0324] Comparative Example 40:

[0325] The solidified soil in this embodiment comprises silt slurry, graphite tailings, sucrose, a main solidifying agent and an alkali activator. The water content of the silt slurry is 40%, the mass of the main solidifying agent is 20% of the mass of the silt slurry, the mass of the graphite tailings is 10% of the mass of the silt slurry, the mass of the sucrose is 3% of the mass of the main solidifying agent, and the mass of the alkali activator is 50% of the mass of the main solidifying agent. After the solidified soil samples are prepared, the cumulative shrinkage strains of the solidified soil samples at 1d, 3d, 7d, 14d and 21d are measured.

[0326] Specifically, the main curing agent in this embodiment includes the following raw materials in terms of mass percentage:

[0327] Slag 69.72%, carbide slag 29.88%, sodium alginate 0.40%

[0328] The base activator in this embodiment includes the following raw materials by mass percentage:

[0329] Sodium silicate 90.90%, polyacrylic acid emulsion 9.10%

[0330] The above-mentioned solidified soil sample preparation method and testing specific process are the same as those of comparative example 38.

[0331] The above comparative examples respectively show the effects of the amount of graphite tailings, the amount of main curing agent, the amount of alkali activator, slag, carbide slag, sodium alginate, sodium silicate and polyacrylic acid emulsion on the resistivity, unconfined compressive strength and cumulative shrinkage strain of cured soil. For the convenience of comparison, the proportions of all comparative examples are summarized in Tables 5, 6 and 7, wherein the amount of graphite tailings and the amount of main curing agent are both percentages of the sludge slurry, the amount of sucrose and the alkali activator are percentages of the main curing agent, the slag, carbide slag and sodium alginate are percentages of the main curing agent, and the sodium silicate and polyacrylic acid emulsion are percentages of the alkali activator.

[0332] Table 5 Comparison of percentage dosage of each component in comparative examples of resistivity

[0333]

[0334] Table 6 Comparison of percentage dosage of each component in the comparative examples of unconfined compressive strength

[0335]

[0336]

[0337]

[0338] Table 7 Comparison of percentage dosage of each component in the comparative examples related to cumulative shrinkage strain

[0339]

[0340] Comparative Examples 1 to 5 were each made in 3 copies for resistivity testing, and the resistivity was tested by an LCR digital bridge, and the resistivity measured in each example was the average value of 3 parallel samples. Comparative Examples 6, 7, 9, and 10 were each made in 3 copies for 28d unconfined compressive strength testing, and Comparative Examples 8, 11 to 36 were each made in 12 copies, and were used for 3d, 7d, 14d, and 28d unconfined compressive strength testing, respectively. The unconfined compressive strength of 3d, 7d, 14d, and 28d was measured according to the method described in the relevant industry standards, and the unconfined compressive strength measured in each example was the average value of 3 parallel samples. Three copies of each of Examples 37 to 40 were prepared for cumulative shrinkage strain tests at 1d, 3d, 7d, 14d and 21d. The cumulative shrinkage strains of the samples at 1d, 3d, 7d, 14d and 21d were measured by referring to the method described in the relevant industry standards. The cumulative shrinkage strain measured in each example was the average value of three parallel samples. The experimental test results are shown in Tables 8, 9 and 10.

[0341] Table 8 Resistivity Related Comparative Example Experimental Results Comparison

[0342]

[0343] Table 9 Comparison of experimental results of unconfined compressive strength related comparative examples

[0344]

[0345]

[0346] Table 10 Comparison of experimental results of comparative examples related to cumulative shrinkage strain

[0347]

[0348] It can be seen from Comparative Examples 1 to 5 that the resistivity of Comparative Examples 1 to 5 decreases with the increase of the graphite tailings content, and the resistivity decreases rapidly when the graphite tailings content is 5% and 10%, and the decrease tends to be gentle after the content is greater than 10%. It can be seen from Comparative Examples 6 to 10 that the 28d unconfined compressive strength of Comparative Examples 6 to 10 decreases with the increase of the graphite tailings content, and the 28d unconfined compressive strength decreases slowly when the content is less than 10%, but when the content is greater than 10%, the 28d unconfined compressive strength drops sharply, and the recommended content of graphite tailings is 5% to 10%.

[0349] It can be seen from Comparative Example 8, Comparative Example 11 to Comparative Example 24 and Comparative Example 36 that with the decrease in the amount of slag and the increase in the amount of carbide slag, the unconfined compressive strength of the samples first increases and then decreases. Except for Comparative Example 8, Comparative Example 13, Comparative Example 14, Comparative Example 15, Comparative Example 20 and Comparative Example 21, the 3d unconfined compressive strength of other samples is lower than the cement-solidified soil strength (Comparative Example 36) at the same dosage level. Therefore, the recommended dosage of slag is 59.76% to 79.68%, and the recommended dosage of carbide slag is 19.92% to 39.84%. As the amount of sodium alginate increases, the unconfined compressive strength of the sample decreases first, then increases, and then suddenly decreases. When the amount of sodium alginate is 0.2% and 0.6%, the unconfined strength of the sample is much lower than that of comparative example 36. When the amount of sodium alginate is 0.4%, the unconfined compressive strength of the sample is not much different from that of the sample without sodium alginate. Therefore, the recommended amount of sodium alginate is 0.4%.

[0350] It can be seen from Comparative Example 8, Comparative Example 25 to Comparative Example 27 and Comparative Example 33 to Comparative Example 36 that the unconfined compressive strength of the sample increases with the increase of the main curing agent dosage. When the main curing agent dosage is 5% and 10%, the 3d unconfined compressive strength of the sample is lower than the cement-solidified soil strength at the same dosage level (Comparative Example 33 and Comparative Example 34). When the main curing agent dosage is 15%, the unconfined compressive strength of the sample is higher than the cement-solidified soil strength at the same dosage level (Comparative Example 35). When the main curing agent dosage is 20%, the unconfined compressive strength of the sample is much higher than the cement-solidified soil strength at the same dosage level (Comparative Example 36). Therefore, the recommended dosage of the main curing agent is 15% to 20%.

[0351] It can be seen from Comparative Example 8, Comparative Example 28, Comparative Example 29 and Comparative Example 36 that the unconfined compressive strength of the sample first increases and then decreases with the increase of the alkali activator dosage, reaching a peak value near 50%. When the alkali activator dosage is 60%, the 3d unconfined compressive strength of the sample is lower than the cement-solidified soil strength with the same dosage level (Comparative Example 36), so the recommended dosage of the alkali activator is 40% to 50%.

[0352] It can be seen from Comparative Example 8 and Comparative Example 30 to Comparative Example 32 that the unconfined compressive strength of the sample first increases and then decreases with the decrease of sodium silicate and the increase of the polyacrylic acid emulsion dosage, reaching a peak value near 9.10% of the polyacrylic acid emulsion dosage. When the polyacrylic acid emulsion dosage is greater than 16.70%, the unconfined compressive strength of the sample decreases sharply. Therefore, the recommended dosage of sodium silicate is 83.30% to 90.90%, and the recommended dosage of polyacrylic acid emulsion is 9.10% to 16.70%.

[0353] It can be seen from Comparative Examples 37 to 40 that the cumulative shrinkage strains of Comparative Examples 38, 39 and 40 are all smaller than those of Comparative Example 37, among which the cumulative shrinkage strain of Comparative Example 40 is the smallest. It can be seen that the addition of sodium alginate and polyacrylic acid emulsion can significantly reduce the shrinkage strain of the solidified soil and reduce the occurrence of cracks.

[0354] In summary, the curing agent formula in this embodiment includes graphite tailings, sucrose, curing agent and alkali activator. The mass of the main curing agent is 15% to 20% of the mass of the sludge slurry, the mass of the graphite tailings is 5% to 10% of the mass of the sludge slurry, the mass of sucrose is 3% of the mass of the main curing agent, and the mass of the alkali activator is 40% to 50% of the mass of the main curing agent. The main curing agent formula includes 59.76% to 79.68% slag, 19.92% to 39.84% carbide slag, and 0.40% sodium alginate by mass percentage. The alkali activator formula includes 83.30% to 90.90% sodium silicate and 9.10% to 16.70% polyacrylic acid emulsion by mass percentage. The graphite tailings, slag, and carbide slag used are all industrial solid wastes, which can effectively utilize solid waste resources, reduce construction costs, and are beneficial to environmental protection. During the solidification process, graphite tailings of corresponding mass ratio are added to improve the conductivity of the soil, and the moisture content of the soil is reduced to a range that is convenient for solidification through electroosmosis drainage, which can reduce the use of curing agent and alkaline activator and improve construction efficiency. Sucrose can delay the medium effect of water in geological polymerization reaction and provide sufficient time for electroosmosis drainage. Slag, carbide slag and sodium alginate are added to the curing agent, and based on the interaction between the raw material components of the curing agent, the activity of each component of the alkaline environment activator is stimulated to make each component react with each other to enhance the strength of the solidified soil. At the same time, the addition of sodium alginate and polyacrylic acid emulsion can improve the microstructure of the solidified soil to a certain extent, hinder the initiation and development of cracks, and reduce shrinkage and cracks.

[0355] Embodiment 2:

[0356] This embodiment provides a method for using a dredger fill solidifying agent for accelerating electroosmosis drainage, using the dredger fill solidifying agent described in Example 1, comprising:

[0357] S1. Remove surface weeds before construction, use positioning rods to determine the location of the metal electrode according to the design, then drive the metal electrode to the designed depth and install the drainage pipe.

[0358] S2. According to the silt soil engineering volume of the block, calculate the required material mass of the block according to the proportion, and weigh the corresponding mass of graphite tailings, sucrose, slag, carbide slag, sodium alginate, sodium silicate and polyacrylic acid emulsion.

[0359] S3. Put the slag, carbide slag and sodium alginate into a mixer and stir them. Put the main curing agent obtained after stirring evenly into a curing agent barrel for storage and standby use.

[0360] S4. Put the sodium silicate and polyacrylic acid emulsion into a blender and stir them. Put the evenly stirred alkali activator into an alkali activator barrel and let it stand for use.

[0361] S5. Add graphite tailings and sucrose to the target block in sequence, and then connect the feeding pipe of the stirring device to the curing agent barrel and the alkali activator barrel respectively. While starting the stirring device, control the main curing agent and alkali activator to be sprayed into the silt soil. Under the action of the stirring device, the main curing agent and alkali activator are evenly mixed with the silt soil. At the same time, the stirring device is driven by the mechanical arm of the excavator to move into the soil, and the stirring, sinking and lifting to the designed depth are repeated until the injection amount of the main curing agent and alkali activator reaches the designed requirement. After stopping the spraying, lift it to the ground, and stir and mix it thoroughly again through the stirring head.

[0362] S6. After the mixture is stirred and mixed evenly, the negative pole of the power supply is connected to the metal electrode to form an electroosmotic drainage system and start electroosmotic drainage.

[0363] S7. When the drainage time reaches the requirement, pull out the drainage pipe and metal electrode, and the construction is completed.

[0364] Optionally, the stirrer speed should be set to >800r / min during stirring in step S3 and step S4, and the stirring time should be 3 to 5min. In step S5, the rotation speed of the stirring head is controlled at 35 to 50r / min, and the sinking speed of the stirring head is controlled at 0.5 to 0.8m / min. The spraying is continued during the stirring and sinking process; after each spraying for 30s, the stirring device is lifted at a uniform speed, and the lifting speed is controlled within 1.0m / min. During the lifting and stirring process, the main curing agent and the alkali activator are sprayed simultaneously, and the height is raised to 0.5m above the design elevation. The drainage time in step S7 is generally 12 to 14h.

[0365] Embodiment 3:

[0366] This embodiment provides a dredger fill, using the dredger fill solidifying agent as described in Example 1; optionally, the dredger fill solidifying agent as described in Example 1 is added to existing dredger fill.

[0367] The above description is only a preferred embodiment of the present embodiment and is not intended to limit the present embodiment. For those skilled in the art, the present embodiment may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present embodiment shall be included in the protection scope of the present embodiment.

Claims

1. A dredger fill solidifying agent for accelerating electroosmosis drainage, characterized in that: The formula of the curing agent includes graphite tailings, sucrose, a main curing agent and an alkali activator; wherein the mass of the main curing agent is 15% to 20% of the mass of the sludge slurry, the mass of the graphite tailings is 5% to 10% of the mass of the sludge slurry, the mass of the sucrose is 3% of the mass of the main curing agent, and the mass of the alkali activator is 40% to 50% of the mass of the main curing agent.

2. A dredger fill solidifying agent for accelerating electroosmosis drainage as claimed in claim 1, characterized in that: The raw materials of the main curing agent are: 59.76% to 79.68% of slag, 19.92% to 39.84% of carbide slag and 0.40% of sodium alginate.

3. A dredger fill solidifying agent for accelerating electroosmosis drainage as claimed in claim 2, characterized in that: The raw materials of the alkali activator are: 83.30% to 90.90% of sodium silicate and 9.10% to 16.70% of polyacrylic acid emulsion.

4. A dredger fill solidifying agent for accelerating electroosmosis drainage as claimed in claim 3, characterized in that: The rotation of the sucrose ratio is 66.3°~67.0°; the main chemical components of the slag are CaO, SiO2 and Al2O3, with a mass fraction of ≥90.00% and a specific surface area of ​​≥450m 2 / kg; the main component of the carbide slag is Ca(OH)2, and its mass fraction is ≥90%; the viscosity of the sodium alginate is 1.05Pa·s~1.15Pa·s, the pH value is 7~8, and the water-insoluble matter is ≤0.10%; the molecular formula of the sodium silicate is Na2O·nSiO2, the soluble solid content is ≥99.00%, the iron content is ≤0.015%, the aluminum oxide content is ≤0.0015%, and the modulus is 3.41~3.70; the pH value of the polyacrylic acid emulsion is 6~7, the molecular weight is 3000~5000, and the solid content is ≥30%.

5. A method for using a dredger fill solidifying agent to accelerate electroosmosis drainage, characterized in that: The dredger fill solidifying agent according to any one of claims 1 to 4 is used, comprising: Before construction, clean the surface, determine the location of the metal electrode, then drive the metal electrode to the designed depth and lay the drainage pipe; According to the silt soil engineering volume of the block, the required material mass of the block is calculated according to the proportion, and the corresponding mass of graphite tailings, sucrose, slag, carbide slag, sodium alginate, sodium silicate and polyacrylic acid emulsion is weighed; The slag, carbide slag and sodium alginate are stirred and evenly mixed to obtain a main curing agent; The sodium silicate and polyacrylic acid emulsion are stirred to obtain an alkali activator after being stirred evenly; Graphite tailings and sucrose are added to the block in sequence, and then the main curing agent and alkali activator are sprayed into the silt soil with the help of a stirring device to evenly mix the main curing agent, alkali activator and silt soil; at the same time, the stirring device is moved toward the inside of the soil, and the stirring, sinking and lifting to the designed depth are repeated until the injection amount of the main curing agent and alkali activator reaches the designed required amount, and stirring and mixing are performed again; After stirring and mixing evenly, connect the negative pole of the power supply to the metal electrode to perform electroosmotic drainage; When the drainage time reaches the requirement, the construction is completed.

6. The method for using a dredger fill solidifying agent for accelerating electroosmosis drainage as claimed in claim 5, characterized in that: The slag, carbide slag and sodium alginate are put into a mixer and stirred; and the sodium silicate and polyacrylic acid emulsion are put into a mixer and stirred.

7. The method for using a dredger fill solidifying agent for accelerating electroosmosis drainage as claimed in claim 6, characterized in that: When the main curing agent and the alkali activator are obtained, the stirring speed of the stirrer is >800r / min, and the stirring time is 3min to 5min.

8. The method for using a dredger fill solidifying agent for accelerating electroosmosis drainage as claimed in claim 5, characterized in that: When the main curing agent and alkali activator are sprayed into the silt soil with the help of a stirring device, the rotation speed of the stirring device is controlled at 35r / min~50r / min, and the sinking speed of the stirring head is controlled at 0.5m / min~0.8m / min; after each spraying for 30s, the stirring device is lifted at a uniform speed, and the lifting speed is controlled within 1.0m / min. During the lifting and stirring process, the main curing agent and alkali activator are sprayed simultaneously, and the height is lifted to 0.5m above the design elevation.

9. The method for using a dredger fill solidifying agent for accelerating electroosmosis drainage as claimed in claim 5, characterized in that: The drainage time is 12h~14h.

10. A dredger fill, characterized in that: The dredger fill solidifying agent as described in any one of claims 1 to 3 is used.